Domestic science in public schools - Spohr, Wilhelmina (My University, 1897)
Introduction: “What then does cooking mean? It means the knowledge of Circe and of Media and of Calypse and of Helen and of the Queen of Sheba. It means a knowledge of all herbs, fruits, balms, spices and all that is healing and sweet in fields and groves and savory in meals. It means carefulness, and inventiveness, and watchfulness and willingness and readiness of appliances. It means the economy of your great-grandmother, and the science of modern chemists. It means much tasting and no wasting. It means English thoroughness and French art and Arabian hospitality, and it means in fine that you are to be perfectly and always ladies, loaf-givers, and that you are to see that every body has something nice to eat” Rushkin. The importance of good cookery as a means of promoting health and happiness was formerly very much undervalued by many house keepers especially those of America. Of course it was understood there must be enough to eat but the quality of food was considered of much less consequence. The tastes of many house wives was more to the display of fine china, silver, and linen—things which delighted the eye, and were of importance, but could not satisfy a hungry mean, make the strong man nor promote friendship and good humor.
Citation: Spohr, Wilhelmina. Domestic science in public schools. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Domestics education; Cooking; Public schools; Theses; Manuscripts (documents)